2020
DOI: 10.1590/1678-4162-11855
|View full text |Cite
|
Sign up to set email alerts
|

Quality enhancement of frozen Nile tilapia fillets using rosemary and thyme oil

Abstract: The food industry and the frozen fish sector in particular have benefitted greatly from advancements in food processing technologies. This study investigated the effect of adding natural antioxidants such as rosemary and thyme oil to frozen fillets of Nile tilapia (Oreochromis niloticus) in order to preserve their quality for consumers. Fillets were treated with rosemary and thyme at two concentrations (1% and 1.5%) and then were stored at 4°C. Samples were analyzed over 4 days for bacteriological (aerobic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Our findings were consistent with those reported by Elhafez et al [75], who observed significant improvement in sensory scores, including color, texture, and odor of Nile tilapia fish fillet treated with 1.5% rosemary oil. The high color and flavor scores in rosemarytreated samples obtained in this study could be correlated to the antioxidant components that delay pigment and lipid oxidation, as well as the volatile oils that are responsible for flavor (Table 3).…”
Section: Sensory Characteristics Of Basa Fish Filletssupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with those reported by Elhafez et al [75], who observed significant improvement in sensory scores, including color, texture, and odor of Nile tilapia fish fillet treated with 1.5% rosemary oil. The high color and flavor scores in rosemarytreated samples obtained in this study could be correlated to the antioxidant components that delay pigment and lipid oxidation, as well as the volatile oils that are responsible for flavor (Table 3).…”
Section: Sensory Characteristics Of Basa Fish Filletssupporting
confidence: 93%
“…Nonetheless, juiciness scores were significantly (p < 0.05) decreased in a groups except rosemary-treated samples during the entire chilling storage com control ones, which could be due to the increase in their cooking loss % (Figu also clear that the results of sensory scores substantiated the data of shear force values (Table 6) as well as cooking loss % (Figure 1). Our findings were consistent with those reported by Elhafez et al [75], who observed significant improvement in sensory scores, including color, texture, and odor of Nile tilapia fish fillet treated with 1.5% rosemary oil. The high color and flavor scores in rosemary-treated samples obtained in this study could be correlated to the antioxidant components that delay pigment and lipid oxidation, as well as the volatile oils that are responsible for flavor (Table 3).…”
Section: Sensory Characteristics Of Basa Fish Filletssupporting
confidence: 93%
“…The TVB-N value was determined referring to the method of Cao et al [ 24 ]. The fish meat was left to spread in 10 times of water for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were also observed by Khalafalla et al ( 2015 ), who reported that the application of Rosmarinus officinalis and Thymus vulgaris extracts significantly reduced the formation of TVB‐N in Nile tilapia fillets during refrigerated storage. Elhafez et al ( 2020 ) also reported that TVB‐N values of rosemary and thyme oil‐treated Nile tilapia fillets were significantly lower than untreated fillets during storage in refrigerated conditions.…”
Section: Resultsmentioning
confidence: 96%